2019
DOI: 10.1016/j.sna.2019.05.044
|View full text |Cite
|
Sign up to set email alerts
|

What retards the response of graphene based gaseous sensor

Abstract: Graphene based sensor to gas molecules should be ultrasensitive and ultrafast because of the single-atomic thickness of graphene, while the response is not fast. Usually, the measured response time for many molecules, such as CO, NH 3 , SO 2 , CO 2 and NO 2 and so on, is on the scale of minutes or longer. In the present work, we found via ab initio calculations there exists a potential barrier larger than 0.7 eV that hinders the gas molecule to land directly at the defective sites of graphene and retards the r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Apart from graphene, the graphene derivative like reduced graphene oxide (rGO) is also being explored for gas sensing applications owing to its facile preparation and novel applications for gas molecule detection [13,14]. Many gas sensors based on rGO have been recently reported for the detection of various gases, such as CH4, H2, CO2, CO, NO2, NH3, and H2S [12,[15][16][17][18]. But, the sensor with fast response and recovery time at room temperature is limitedly reported.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from graphene, the graphene derivative like reduced graphene oxide (rGO) is also being explored for gas sensing applications owing to its facile preparation and novel applications for gas molecule detection [13,14]. Many gas sensors based on rGO have been recently reported for the detection of various gases, such as CH4, H2, CO2, CO, NO2, NH3, and H2S [12,[15][16][17][18]. But, the sensor with fast response and recovery time at room temperature is limitedly reported.…”
Section: Introductionmentioning
confidence: 99%
“…Because gas sensors need time to respond to the analytes, there is a relationship between measurement speed and signal magnitude–typically, the faster the measurement, the smaller the signal. Even sensor materials with theoretically rapid response time such as graphene are limited in how quickly they can respond to brief exposures to the analyte: It has been suggested that adsorption barriers prevent some gas molecules from landing directly on graphene’s defect sites, causing the responses to be diffusion limited . Indeed, long response times are seen in the graphene-based gas sensor array literature, where response times can vary between 30 s and 20 min. ,,,, Improving this even further could enhance graphene’s utility in sensing.…”
mentioning
confidence: 99%